La ricerca del bosone di Higgs - Casalbuoni, Roberto (Lectio Magistralis, 2013)
This volume describes the history of research that led to the experimental evidence of the Higgs boson, officially announced by CERN in Geneva on July 4, 2012. This discovery represented the culmination of a journey that began with the discovery of radioactivity in 1896, and which led to the conjecture of a new interaction: the weak interaction. The attempts to understand this new type of strength are retraced narrating the difficulties, the momentary satisfactions and disillusions of these studies that have been carried out over a period of more than one hundred years. Experimental research that led to reconsidering the existence of the Higgs particle is also illustrated, highlighting, in particular, what has been done at CERN's proton accelerator, LHC (Large Hadron Collider), where the discovery took place.